Inheritance of quantitative resistance to downy mildew (Plasmopara halstedii) in sunflower (Helianthus annuus L.) - Vear, F; Serre, F; Jouan-Dufournel, I; Bert, P. F; Roche, S; Walser, P; Tourvieille de Labrouhe, D; Vincourt, P (Euphytica, 2008)
Quantitative resistance to sunflower downy mildew was studied on inbred lines and hybrids not carrying efficient major gene resistance, in field trials in one to four sites over 3 years. Hybrids from factorial crosses showed that inheritance is under additive control and comparison with reactions of parental inbred lines gave narrow sense heritabilities of 27-57%. Analysis of a polymorphic recombinant inbred line population without efficient major gene resistance indicated that two highly significant Quantitative Trait Loci (QTL) explained 42% of variation in field reaction to downy mildew. These QTL were mapped on linkage groups 8 and 10, and do not appear related to any of the known major resistance gene clusters. Possible bases of this type of resistance and its use in breeding are discussed.